KEUNIKAN TRADISI PERTUNANGAN MASYARAKAT PADANG PARIAMAN - Taufik Hidayat; Yusri Amir (Turast: Jurnal Penelitian dan Pengabdian, 2022)
One of the unique traditions in the casting process in the Padang Pariaman community is "Mamak to Mamak marriage". This tradition has been passed down from generation to generation and is an obligation at the traditional engagement ceremony. If this tradition is not carried out, it will affect the continuation of the engagement process and even affect the marriage process. This research is empirical research by looking at the tradition of "Mamak and Mamak Marriage" in the Padang Pariaman community. The meaning of the tradition "Marriage between mamak and mamak" is "The bond between two tribal mamak in zahir and the engagement between their nephews is essentially a marriage requirement for the legitimacy of the relationship between two families, tribes and villages. The marriage procession between mamak and mamak begins with a marriage sermon, the marriage contract and ends with the exchange of "tando" engagement as a form of traditional engagement. As a result of the law, customary family relations are established and receive customary sanctions in the event of termination of the engagement.